Creep test facility development and creep analysis of braced composite cross arms in 132 kV transmission tower - Muhammad Rizal, Muhammad Asyraf (2021)
Previously, most of cross arms in 132 kV latticed suspension towers made of wood timber cross arms to sustain electrical cables and insulators above the ground. However, wood timber cross arms seemed to degrade and fail after 20 years of service due to creep, natural wood defect and attack from natural enemies. This issue has brought the urgency to replace the previous cross arms with pultruded glass fibre reinforced polymer composite (PGFRPC) cross arms due to better strength, lightweight, and low degradability. To date, no study has been conducted on the evaluation of creep properties of cross arms’ material and structure for long-term service application. Moreover, the creep testing facilities specialising in cross arms are still undeveloped to conduct the creep test for outdoor use. Lastly, no research has been conducted on the enhancement of cross arm structure by retrofitting with additional braced arms to improve creep resistance performance. It is reported on the development and characterization of creep responses of PGFRPC cross arms. Initially, a hybrid TRIZ-Morphological Chart-ANP method was implemented to develop the conceptual design for both multi-operation flexural and cantilever beam creep test rigs. From the product design specifications (PDS), concept designs 3 and 5 were selected as the final design concept for multi-operation flexural and cantilever beam creep test rigs, respectively. For three-point flexural creep analysis, it started with quasi-static flexural test and found out the modulus of elasticity of PGFRP almost the same value as Balau wood. In contrast, the flexural strength of pultruded GFRP increases about 72.97 % compared to Balau wood. This finding further established that PGFRP composite permitted better creep resistance as the creep strain increases about 100% in Balau wood as compared to PGFRP composite. This is due to low creep strain and better stability of transition of elastic to viscoelastic phase. These creep results for both wood and composite cross arms were optimized with Findley model, and two general creep equations was generated. For the cantilever beam creep results, it was illustrated that both wood and composite cross arms exhibited less creep strain after retrofitting with additional braced arms. Furthermore, the creep resistance performance for both braced wood and composite cross arms improved about 15 to 21 % higher. This is due to higher structural integrity and more stable elastic transition to viscoelastic phases. Further numerical analyses demonstrated that the stress-independent material exponent exhibited approximately the same values between right and left arms, and higher elastic, and viscoelastic performance for both braced wood and composite cross arms under long-term creep. To summarise, PGFRPC cross arms have been revealed to have better mechanical strength and creep resistance performances, which is suitable to replace wood cross arms. In addition, the enhancement of PGFRPC cross arms by incorporating bracing system contributes to significant improvement of creep resistance and mechanical performances for the current design.